Colonial Inheritance and Educational Inequity: An Analysis of the English-Only Curriculum in Postcolonial Zambia (British Journal of Multidisciplinary and Advanced Studies, 2025)
This paper critically examines the enduring impact of colonial language policies on Zambia’s education system, demonstrating how an English-only curriculum perpetuates linguistic hierarchies, marginalizes Indigenous knowledge, and deepens socioeconomic inequities. Drawing on postcolonial theory and Afrocentric notions of Ubuntu, I conduct a document review of key policy texts—including the Education Act of 2011 and the 2023 Zambia Education Curriculum Framework—alongside relevant scholarly literature and comparative case studies. My analysis highlights both the historical roots of these inequities and practical pathways to decolonize the curriculum by integrating local languages and community-centered pedagogies.